Eutectic solvent-based bioactive films functionalized with microbial astaxanthin extends shelf life of fresh strawberries - Mussagy, Cassamo U.; Farias, Fabiane O.; Sasaki, Josana C. [UNESP]; Scontri, Mateus [UNESP]; Picheli, Flavio [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; de Azeredo, Henriette M.C.; Pessoa, Adalberto; Herculano, Rondinelli D. [UNESP] (My University, 2023)
Food waste and consumers safety are critical concerns that necessitate the development of improved packaging systems, such as those involving the use of edible films and coatings, which may act as primary packaging, helping the external (secondary) packaging in its protecting role. However, current options of films/coatings have limitations, such as inefficient plasticizer agents and the need for high levels of active ingredients. To address these challenges, we have created a new packaging material formulated with bio-based sodium alginate (SA) and choline-based deep eutectic solvents (DES), which are eco-friendly and capable of packaging food substrates to enhance their safety and longevity. Using a SA-DES materials we incorporated naturally derived microbial products (astaxanthin - AXT) with antioxidant and antimicrobial properties and evaluated the mechanisms behind the formation of coatings. Our results demonstrate that strawberries coated with alginate-choline chloride:glycerol (SA-[Ch]Cl:Gly) had a longer shelf life, inhibited natural microbial proliferation, and lost less weight than uncoated controls at room temperature. This study demonstrated that DES are a promising and sustainable solution for cost-effective, and biodegradable environmentally friendly packaging systems.
Keywords: Active packaging; Edible coatings; Polysaccharides